2019
DOI: 10.1097/ta.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Human neural stem cell transplant location–dependent neuroprotection and motor deficit amelioration in rats with penetrating traumatic brain injury

Abstract: BACKGROUND Penetrating traumatic brain injury induces chronic inflammation that drives persistent tissue loss long after injury. Absence of endogenous reparative neurogenesis and effective neuroprotective therapies render injury-induced disability an unmet need. Cell replacement via neural stem cell transplantation could potentially rebuild the tissue and alleviate penetrating traumatic brain injury disability. The optimal transplant location remains to be determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…They transplanted hNSCs into the core or around the lesion one week after the injury. After 12 weeks, neuronal differentiation and motor function improvement were observed in both groups but sparing of a larger volume of intact brain including cortex makes the peri-lesion administration a preferable choice [40]. Beretta et al made an attempt to see the effects of hNSCs on posttraumatic hyperexcitable brain.…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…They transplanted hNSCs into the core or around the lesion one week after the injury. After 12 weeks, neuronal differentiation and motor function improvement were observed in both groups but sparing of a larger volume of intact brain including cortex makes the peri-lesion administration a preferable choice [40]. Beretta et al made an attempt to see the effects of hNSCs on posttraumatic hyperexcitable brain.…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…Endogenous neurogenesis is limited due to the challenging environment after TBI [ 28 , 29 ]. Recently, NSCs have been successfully transplanted into TBI model rodents and shown to result in a significant improvement in neurological function [ 10 , 11 , 12 ]; however, clinical translation is still lacking. With TBI as a major cause of emergencies, different phases of TBI are drastically varying microenvironments to grafted NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reconstructing the injured neuron circuit through grafting neural stem cells (NSCs) has been considered aa a promising cell therapy for TBI [ 8 , 9 ]. In a rodent TBI model, NSC transplantation has shown an improvement of cognitive and motor functions [ 10 , 11 , 12 ]. Recent studies also applied various growth factors, e.g., BDNF, GDNF, and bFGF, to promote the viability of grafted NSCs under TBI conditions [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a cascade of biochemical and cellular processes in the acute-subacute stages that can be affected by transplanted NPCs with reduced degeneration as a result. Several transplantation studies of murine 40 and human 41 , 42 NPCs have shown improved functional recovery that can be attributed to neuroprotection, that is, reduced degeneration of compromised host neurons. Neuroprotection is a key mechanism by which fNPCs can improve functional outcomes after experimental SCI, and human fNPCs derived from the spinal cord are more effective than fNPCs from the forebrain.…”
Section: Cell Transplantation In Cns Traumamentioning
confidence: 99%